2020
DOI: 10.3390/ijerph17186613
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study Exploring Menstruation Experiences and Practices among Adolescent Girls Living in the Nakivale Refugee Settlement, Uganda

Abstract: (1) Background: Girls in low- and lower-middle income countries face challenges in menstrual health management (MHM), which impact their health and schooling. This might be exacerbated by refugee conditions. This study aimed at describing menstruation practices and experiences of adolescent girls in Nakivale refugee settlement in Southwestern Uganda. (2) Methods: We conducted a qualitative study from March to May 2018 and we intentionally selected participants to broadly represent different age groups and coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 16 publications
2
40
0
Order By: Relevance
“…In addition, it was described that those adolescents and young women in humanitarian settings can suffer sexual exploitation trying to manage their MHM needs [ 10 , 22 ]. In our study, we observed that the majority of females reported fear and anxiety of leakage of bleeding through the clothes which was also reported in other humanitarian contexts causing psychological and social effects as harassment, isolation, and absenteeism at school [ 9 , 10 , 25 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…In addition, it was described that those adolescents and young women in humanitarian settings can suffer sexual exploitation trying to manage their MHM needs [ 10 , 22 ]. In our study, we observed that the majority of females reported fear and anxiety of leakage of bleeding through the clothes which was also reported in other humanitarian contexts causing psychological and social effects as harassment, isolation, and absenteeism at school [ 9 , 10 , 25 ].…”
Section: Discussionsupporting
confidence: 62%
“…Almost 30% of them did not answer the questions or answered that they did not know what menstruation for them is; moreover, for the others, menstruation was associated either with negative feelings or resignation. This has been described in other studies regardless the nationality, religious, or cultural beliefs [ 9 , 10 , 22 – 25 ], underlying the needs of education on menstrual and reproductive health with the youth and the communities, so that everyone, including men, would be knowledgeable and comfortable in discussing MHM issues [ 10 , 22 , 27 ].…”
Section: Discussionmentioning
confidence: 85%
“…availability of soap for washing [20,33,49,53,54,[56][57][58]60,61,63,64,66,67,73,77,90,91] and the availability of a physically functional disposal mechanism and/or service for used material [18,28,[31][32][33][34][35][36][37]42,[44][45][46][47][48]52,53,57,58,60,62,63,[66][67][68]71,76,77,82,83,86,90,91,…”
Section: Plos Onementioning
confidence: 99%
“…During menstruation, women use different menstrual products to absorb menstrual blood and prevent outflow. The use of menstrual products can be traced back to ancient times, when women used leaves, hay, and bark, which are easy to clean, to carry menstrual blood due to poor living conditions [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. However, women in different countries dealt with menstrual blood in different ways, including the use of wool, folded paper, and papyrus.…”
Section: Introductionmentioning
confidence: 99%